2001
DOI: 10.1063/1.1384448
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fast fiber-optic two-color pyrometer for the temperature measurement of surfaces with varying emissivities

Abstract: A two-color pyrometer has been developed to measure the temperature of surfaces with unknown emissivities during high speed turning processes. Quartz fibers enable measurements at locations with limited optical access. The sensitivity of the pyrometer has to be high enough to measure temperatures down to 300 °C of an aluminum alloy with an emissivity as low as 0.2. The accuracy of the two-color pyrometer has been compared with the accuracy of monochromatic pyrometers for different metallic surfaces. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 12 publications
0
77
0
2
Order By: Relevance
“…Only a small number of layers are shown; in reality, foils contain hundreds of layers. A two-color pyrometer, similar to one described in [50], was used to compare reaction temperatures as a function of time for the three chemistries. During these temperature measurements, samples were held vertically with the top and bottom edges clamped between glass slides to prevent the foils from folding during the reaction while minimizing heat-sinking effects.…”
Section: Reaction Heats Temperatures and Productsmentioning
confidence: 99%
“…Only a small number of layers are shown; in reality, foils contain hundreds of layers. A two-color pyrometer, similar to one described in [50], was used to compare reaction temperatures as a function of time for the three chemistries. During these temperature measurements, samples were held vertically with the top and bottom edges clamped between glass slides to prevent the foils from folding during the reaction while minimizing heat-sinking effects.…”
Section: Reaction Heats Temperatures and Productsmentioning
confidence: 99%
“…Monochromatic pyrometers were also not considered here because calculations showed that slight changes of the surface properties can result in large errors [5], and also signal attenuation or unknown object sizes result in measurement errors.…”
Section: Pyrometer Conceptmentioning
confidence: 99%
“…Such non-streaked two-color pyrometers usually show better accuracy than their one-color counterparts [24]. As such, a two-color SOP is desired.…”
Section: Sample Temperature Diagnosticsmentioning
confidence: 99%